Perlindungan Pihak Ketiga Beriktikad Baik Dalam Non-Conviction Based Asset Forfeiture - Fadhila, Yanuar Ramadhana (Universitas Semarang, 2025)
This study critically examines the legal framework governing non-conviction-based asset forfeiture (NCB) in Indonesia, with particular emphasis on the protection of bona fide third parties. Despite its strategic role in asset recovery for combating corruption, the implementation of NCB has generated significant legal uncertainty due to normative disharmony among national regulations, including anti-corruption laws, anti-money laundering laws, criminal procedural law, Supreme Court Regulations, and the Draft Asset Forfeiture Bill. This study employs a normative juridical method using statutory and conceptual approaches to analyze the extent to which existing regulations safeguard third-party property rights in accordance with due process of law and the presumption of innocence. The findings reveal that the absence of clear legal parameters defining bona fide third parties, disproportionate evidentiary burdens, and restrictive objection mechanisms has weakened legal protection and increased the risk of constitutional rights violations. The novelty of this research lies in proposing a reconstructed legal framework for NCB asset forfeiture by formulating objective indicators of good faith, proportional standards of proof, reasonable time limits for objections, and strengthened judicial oversight. The study contributes theoretically to the development of a balanced asset forfeiture model that harmonizes state interests in asset recovery with individual property rights, while practically offering regulatory reform recommendations to enhance legal certainty, procedural fairness, and the legitimacy of asset recovery mechanisms in Indonesia. Penelitian ini mengkaji secara kritis kerangka hukum non-conviction based asset forfeiture (NCB) di Indonesia dengan menitikberatkan pada perlindungan hukum bagi pihak ketiga yang beriktikad baik. Meskipun NCB memiliki peran strategis dalam pemulihan aset hasil tindak pidana korupsi, implementasinya masih menimbulkan ketidakpastian hukum akibat disharmoni normatif antara berbagai regulasi nasional, termasuk undang-undang pemberantasan korupsi, tindak pidana pencucian uang, hukum acara pidana, peraturan Mahkamah Agung, serta Rancangan Undang-Undang Perampasan Aset. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual untuk menganalisis sejauh mana perlindungan hak milik pihak ketiga telah sejalan dengan prinsip due process of law dan asas praduga tidak bersalah. Hasil penelitian menunjukkan bahwa ketiadaan parameter hukum yang jelas mengenai iktikad baik, pembebanan pembuktian yang tidak proporsional, serta mekanisme keberatan yang terbatas telah melemahkan perlindungan hukum dan berpotensi melanggar hak konstitusional pihak ketiga. Kebaruan penelitian ini terletak pada perumusan rekonstruksi kerangka hukum perampasan aset berbasis NCB melalui penetapan indikator objektif iktikad baik, standar pembuktian yang proporsional, jangka waktu keberatan yang rasional, serta penguatan peran pengawasan yudisial. Secara teoretis, penelitian ini berkontribusi pada pengembangan model perampasan aset yang berkeadilan, sedangkan secara praktis menawarkan rekomendasi pembaruan regulasi guna meningkatkan kepastian hukum, keadilan prosedural, dan legitimasi mekanisme asset recovery di Indonesia.